Diagnostic evaluation of LTA and suPAR as combined biomarkers for multidrug-resistant Gram-positive infections: a case-control study in Iraq - Khalife, Mohammed Sadeq; Ali, May Mohammed; Al-Hasnawi, Sawsan M. Jabbar; Hawas, Basit Khaled (Pharmakeftiki, 2025)
Antimicrobial resistance (AMR) has emerged as a critical threat to global public health. Timely and accurate identification of resistant pathogens (followed by appropriate antimicrobial therapy and robust stewardship) is essential in order to curb the emergence and spread of AMR. Although current diagnostic modalities offer clinical value, they are constrained by time requirements and limited capacity to differentiate colonization from active infection. Lipoteichoic acid (LTA), specific to Gram-positive bacteria, serves as a direct indicator of bacterial presence. In parallel, the soluble urokinase-type plasminogen activator receptor (suPAR) reflects host immune response, providing insight into infection severity and progression. This study investigates the diagnostic and prognostic utility of a dual biomarker panel comprising LTA and suPAR for the rapid assessment of bacterial infections. In a case–control design, we have quantified the serum levels of LTA and suPAR by ELISA in 62 patients with confirmed bacterial infections and 38 matched controls. Statistically significant elevations were observed in patients with extensively drug-resistant (XDR) infections: LTA levels reached 54.47 ng/L (p=0.0111), and suPAR levels reached 284.74 ng/mL (p=0.0019), compared to the multidrug resistant (MDR) infection and the non-MDR infection groups. These findings underscore the potential of LTA and suPAR as complementary biomarkers for the early detection and stratification of bacterial infections.